2002
DOI: 10.1007/s00438-002-0662-9
|View full text |Cite
|
Sign up to set email alerts
|

C-to-U conversion in the intercistronic ndhI/ndhG RNA of plastids from monocot plants: conventional editing in an unconventional small reading frame?

Abstract: Editing of plastid RNAs proceeds by C-to-U, in hornwort species also by extensive U-to-C, transitions, which predominantly lead to the restoration of codons for structurally and/or functionally important, conserved amino acid residues. So far, only one instance of editing outside coding regions has been reported - in the psbL/ psbF intergenic region of Ginkgo biloba. This site was proposed to have no functional importance. Here we present an evaluation of an editing site in the ndhI/ ndhG intergenic region in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Previously, a C-to-U conversion at the −10 position of the ndhG 5′UTR in monocot plants was predicted to modify the RNA secondary (stem/loop) structure (Drescher et al 2002 ), but was not observed in moth orchid. Instead, a C-to-U substitution at the −30 position of the psbH 5′UTR that can form an energetically less stable secondary structure was reported in moth orchid (Zeng et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a C-to-U conversion at the −10 position of the ndhG 5′UTR in monocot plants was predicted to modify the RNA secondary (stem/loop) structure (Drescher et al 2002 ), but was not observed in moth orchid. Instead, a C-to-U substitution at the −30 position of the psbH 5′UTR that can form an energetically less stable secondary structure was reported in moth orchid (Zeng et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some RNA editing events could result in the creation of translation initiation or termination codons or repair internal stop codons (Bock 2000 ; Fiebig et al 2004 ; Wolf et al 2004 ). Several events occurring in non-coding regions such as tRNA, 5′/3′ untranslated regulatory regions (UTR) or introns might affect RNA stability or splicing by modifying the secondary structure (Drescher et al 2002 ; Farre et al 2012 ; Zeng et al 2007 ). The significance of RNA editing in regulating plant organellar gene expression has been demonstrated, with the alteration of some editing sites having deleteriously effects on plant growth, development, and fertility (Hammani and Giege 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…3B ) and other species [ 5 , 19 , 25 , 59 62 ] appears in some cases to improve intron secondary structure, which is important to increase intron splicing efficiency. Intergenic edit sites in plant organellar transcripts may also have functional importance in some cases, such as regulating translational efficiency [ 7 , 19 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Editing sites have also been detected in the anticodon of tRNA (Leu) and within untranslated regions, including introns. 122,[137][138][139] However, it seems that the frequency of editing within noncoding regions is very low in comparison with the extent of editing within coding regions. The discovery that editing often leads to the conservation of certain amino acid residues in some proteins in both mitochondria and chloroplasts suggests that editing may act as a mechanism to prevent the deleterious effects of point mutations that have been maintained through evolution.…”
Section: Rna Editingmentioning
confidence: 99%